IRRIGATION STRUCTURE TRENDS AND REGIONAL VARIATIONS IN HARYANA STATE: A STUDY ON SOURCES OF NET IRRIGATED AREA FROM 1970-71 TO 2014-15 - Gautam, Ravinder (Research Journal of Agriculture (RJA), 2023)
This article presents a study on the regional variations in the sources of net irrigated area in Haryana state, India. The study covers the period from 1970-71 to 2014-15 and aims to show source-wise irrigation structure trends at the district level. The data used in the study were obtained from various issues of statistical abstracts of Haryana. The results show that the pattern and structure of irrigation in Haryana state have significantly changed over the years, with tubewells and canals being the primary irrigation sources. The adoption of tubewell irrigation varies across different districts according to the technological feasibility and natural setup, with some districts relying heavily on tubewell irrigation. However, overexploitation of groundwater resources has led to a decline in the sustainability of tubewell irrigation in some areas. Canal irrigation has also declined in the study area due to poor performance of surface irrigation systems, market failures, and failures of public sector agencies to deliver irrigation water. The study provides insights into the changing irrigation structure and the factors affecting the sustainability of irrigation sources in Haryana state, which can be useful for policymakers and stakeholders in developing sustainable irrigation practices.